Peran Direktorat Jendral Imigrasi dalam Penanggulangan Tindak Pidana Terorisme - Annisa Febrianti; Ben Reinaldi Rizki Akbar; Putra Deta Husa Prasta (Ideas Publishing, 2021)
The purpose of this study is to seek to expand the immigration management model that can prevent terrorist activities in Indonesia. The study identified links between terrorism including issuance of travel documents, immigration control at the borders of the Republic of Indonesia, issuance of entry permits and visas, adhering to anti-terrorism laws. The research method uses qualitative with literature study. Sources of data taken from the study of journals, laws and relevant books. The findings include that the immigration system is based on three elements: privacy, surveillance, and border control. As a general rule, all three make transactions. The preventive management model should be cyclical in the sense that functionality cannot be shared between the elements that are obligated. To be effective in preventing terrorism, this form of management requires the exchange of information and data between migrants. In addition, all signatures of other agencies (eg police, BNPT, BIN, NCB - Interpol, etc.) are also subject to regulations to ensure the quality of the circulation system. Tujuan dalam penelitian ini berupaya untuk memperluas model manajemen keimigrasian yang dapat mencegah aktivitas teroris di Indonesia. Studi tersebut mengidentifikasi hubungan antara terorisme termasuk penerbitan dokumen perjalanan, pengawasan imigrasi di perbatasan wilayah Republik Indonesia, penerbitan izin masuk dan visa mengikuti undang-undang anti-terorrisme. Metode penelitian menggunakan metode kualitatif dengan studi kepustakaan. Sumber data yang diambil dari kajian jurnal, Undang-Undang dan buku yang relevan. Hasil temuan di antaranya sistem imigrasi didasarkan pada tiga elemen: privasi, pengawasan, dan kontrol perbatasan. Sebagai aturan umum, ketiga melakukan transaksi. Model manajemen pencegahan harus bersiklus dalam arti bahwa fungsionalitas tidak dapat dibagi antara elemen yang berkewajiban. Agar efektif dalam mencegah terorisme, bentuk pengelolaan ini membutuhkan pertukaran informasi dan data antar migran. Selain itu, semua tanda tangan instansi lain (contoh: kepolisian, BNPT, BIN, NCB-Interpol, dsb.,) juga tunduk pada regulasi untuk menjamin kualitas sistem peredaran.